On the Concept of “Lokāntarikā” - Qi, Guanxiong (Journal of International Buddhist Studies, 2024)
Lokāntarikā is one of the strangest places in the Buddhist cosmology. Typically understood as a hell, it is not located in any world system (cakravāla) but in the gap of three world systems. This article will discuss the narratives and depictions of lokāntarikā in early Buddhist canonical and Thai literature. The author argues that lokāntarikā mostly serves as a narrative device to highlight the miraculous qualities of the Buddha. The Traiphum Phra Ruang gives the most nuanced depiction of lokāntarikā, and lokāntarikā appears in Thai classical literature as a part of oath-taking.